El proceso contable en la empresa indumarmol, período 2015 y su incidencia en los estados financieros. - Vallejo Dávalos, María Fernanda (2017)
The accounting process is of vital importance for a company because of its efficiency depends on the quality of the information contained in the financial statements, which as a result of business management are drawn up, presented and shown schematically the changes in its equity accounts and the movement of Their accounts of income and expenses. The research aimed to determine how the accounting process affects the financial statements, period 2015 in the company INDUMARMOL of the city of Guayaquil. The deductive method was used based on the general knowledge of the variables to identify their behavior in the company; The research was non-experimental; Its design was documentary, because accounting and financial documents were reviewed, and field documents were applied when a structured questionnaire was applied. Their level was descriptive because the characteristics of the study population were detailed. The results show that the accounting process affects the financial statements for 2015 in the company INDUMARMOL of the city of Guayaquil.